Factors influencing Saudi young female consumers' luxury fashion in Saudi Arabia: Predeterminants of culture and lifestyles in Neom city - Areej Algumzi (Journal of Risk and Financial Management, 2022)
Saudi Arabia has been taking various initiatives (such as improving women's rights for reduced dependency on male guardians, and creating training opportunities for skills improvement among Saudi locals) for creating an integrated community with diverse cultures and lifestyles as a part of transforming into a knowledge-based economy (Vision 2030). As a part of these initiatives, a new city, the NEOM project, is being constructed in the country, which includes diverse cultures, innovative technologies integrated into the ways of living and working, or simply put, as a new model for sustainable living, working and prospering. This never-before-attempted model in the country may have an impact on the local Saudi culture and lifestyles. In this context, the perceptions towards luxury fashion among the Saudi citizens were identified to be one of the important areas in lifestyles, which may be influenced by progress and development. Therefore, this study identifies and evaluates factors influencing Saudi young female consumers' luxury fashion in Saudi Arabia, which can act as predeterminants of culture and lifestyles in Neom city. An online questionnaire-based survey was used for collecting data related to the various influencing factors classified from the literature review. A random sampling and snowball sampling approach was adopted to select the female participants across all the regions. A final sample of 775 participants was achieved after filtering the incomplete and ineligible responses. The results revealed that both motivational factors and store factors positively influenced the perceptions towards luxury brands, while significant differences were observed between the groups (educated and uneducated; employed and unemployed), while no differences were observed in relation to external factors. It can be concluded that the perception that luxury is intended for the wealthy and affluent was identified to be irrelevant, and there is a strong influence of external factors, such as social norms, religion, culture, and family on young female consumers' luxury fashion in Saudi Arabi.
Keywords: 650; NEOM; marketing; luxury; fashion; influencing factors; motivation; brand